Thiopurines in the Management of Crohn’s Disease: Safety and Efficacy Profile in Patients with Normal TPMT Activity—A Retrospective Study - Amine Benmassaoud; Xuanqian Xie; Motaz AlYafi; Yves Theoret; Alain Bitton; Waqqas Afif; Talat Bessissow (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Thiopurines are used in the treatment of Crohn’s disease (CD) and thiopurine S-methyltransferase (TPMT) activity can guide thiopurine dosing to avoid adverse events. This retrospective study evaluated the safety and efficacy of starting thiopurines at low dose versus full dose in patients with CD and normal TPMT. Methods. This was a single center retrospective study including adult CD patients with normal TPMT levels (≥25 nmol/hr/g Hgb) who were followed for 1 year. Patients started at full dose of azathioprine (2–2.5 mg/kg) or 6-mercaptopurine (1–1.5 mg/kg) were compared to patients started at low dose. Harvey-Bradshaw index, treatment failure, and drug-related adverse events were recorded. Results. Our study included 134 patients. Both groups had similar incidences of drug-related adverse events and discontinuation of therapy due to side effects. Fifty-six percent of all adverse events occurred within 31 days and 92% occurred within 3 months of therapy. Clinical response favored the full-dose group at 6 months (69% versus 27%, p=0.0542). Conclusions. Our study indicates that it is safe to start patients on full-dose thiopurine when they have a normal TPMT given its very similar toxicity profile to patients started on low dose. This may also positively impact efficacy.